2010
DOI: 10.5114/aoms.2010.17087
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of different levels of continuous positive airway pressure on cardiac autonomic modulation in chronic heart failure and chronic obstructive pulmonary disease

Abstract: IntroductionNon-invasive ventilation may improve autonomic modulation and ventilatory parameters in severely disabled patients. The aim of the present study was to evaluate the physiological influence of acute treatment with different levels of continuous positive airway pressure (CPAP) on the autonomic balance of heart and respiratory responses in patients with stable chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF).Materials and methodsA COPD group (n = 10), CHF group (n = 8) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 41 publications
2
44
0
6
Order By: Relevance
“…5,22,37,40 This result is also corroborated by the findings of an earlier study that reported that NIMV has opposing influence on the HRV. 46 Three studies also reported significant increases in the values of LF HRV indices.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…5,22,37,40 This result is also corroborated by the findings of an earlier study that reported that NIMV has opposing influence on the HRV. 46 Three studies also reported significant increases in the values of LF HRV indices.…”
Section: Discussionsupporting
confidence: 82%
“…Eight articles were further excluded for failure to meet all the inclusion criteria. In the end, 18 studies comprising eleven case-controlled, 6,8,10,15,22,[35][36][37][38][39]41 four cohort, 5,19,27,40 and three RCT 20,23,28 studies were included for evidence synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations